Ответ:
2 35/36
Пошаговое объяснение:
[tex]6 \frac{37}{126} - x = 3 \frac{9}{28} \\ 6 \frac{37}{126} - 3 \frac{9}{28} = x \\ 6 \frac{74}{252} - 3 \frac{81}{252} = x \\ 5 \frac{326}{252} - 3 \frac{81}{252} = x \\ 2 \frac{245}{252} = x \\ x = 2 \frac{35}{36} [/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
2 35/36
Пошаговое объяснение:
[tex]6 \frac{37}{126} - x = 3 \frac{9}{28} \\ 6 \frac{37}{126} - 3 \frac{9}{28} = x \\ 6 \frac{74}{252} - 3 \frac{81}{252} = x \\ 5 \frac{326}{252} - 3 \frac{81}{252} = x \\ 2 \frac{245}{252} = x \\ x = 2 \frac{35}{36} [/tex]